Pengembangan Aplikasi Augmented Reality Ter integrasi IoT untuk Visualisasi Desain Arsitektur dan Kontrol IoT - Adhitya Andriansyah Putra; Irman Hariman (Jurnal Dinamika Informatika, 2025)
ABSTRACT The limitations of conventional architectural visualization methods, which only provide a 70% level of understanding, and the gap in the integration of Aug mented Reality (AR) technology with the Internet of Things (IoT) are major challenges in the modern architectural design industry. This research aims to develop an AR application integrated with an IoT system for architectural de sign visualization and smart home device control using a mixed-method approach with the ADDIE development model. The developed system uses Unity 3D as the AR rendering engine, Vuforia SDK for marker detection, NodeMCU ESP8266 integrated with a DHT22 sensor for temperature monitoring, and a relay system for lighting control through the Blynk platform. The testing was conducted on 68 respondents using the System Usability Scale (SUS) instrument, marker de tection accuracy testing, and system latency evaluation. The results showed that the SUS score reached 80.96 (category “Good”), exceeding the minimum target of 70 by a margin of 15.7%. Vuforia marker detection accuracy reached 92% under various lighting conditions, exceeding the 80% target with a very strong correlation (R=0.994). User understanding of the architectural design increased significantly to 85.7% compared to the conventional method, which was only 70% (p<0.05). The real-time temperature monitoring system using the DHT22 sensor achieved an accuracy of ±1°C with updates every 5 seconds, in line with the research target. Although the IoT control latency reached 4000ms, exceeding the target of 1000ms, the system still provided an acceptable interaction experience in the context of a smart home application. This research successfully bridges the gap between AR and IoT technologies within an integrated platform, making a significant contribution to the digital transformation of the architecture industry and the development of a more efficient and interactive smart building ecosystem.